2016
DOI: 10.1002/pola.28212
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyolefin‐block‐polystyrene through sequential coordination and anionic polymerizations

Abstract: Two representative bulk polymers, polyolefin (PO) and polystyrene (PS), were molecularly connected to form POblock-PS by sequentially performing coordination and anionic polymerizations in one pot. Ethylene/1-octene copolymerization was performed using a typical ansa-metallocene catalyst, rac-[Me 2 Si(2-methylindenyl)] 2 ZrCl 2 , in the presence of (benzyl) 2 zinc to grow PO-chains at the Zn site. Anionic styrene polymerization was subsequently performed using nBuLiÁ(tmeda) (tmeda, N,N,N 0 ,N 0 -tetramethyleth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Syntheses of polyethylene-block-polyester and polyethylene-block-polyether have been attempted with POs functionalized with -OH end groups, which were generated by treatment of the CCTP product (polyolefinyl) 2 Zn with O 2 [28][29][30][31]. We also discovered a method to grow polystyrene (PS) chains initiating from (polyolefinyl) 2 Zn that allows the syntheses of commercially more relevant PO-block-PS and PS-block-PO-block-PS in one-pot [32][33][34][35]. In those works, n-BuLi•(TMEDA) (TMEDA = tetramethylethylenediamine, i.e., Me 2 NCH 2 CH 2 NMe 2 ) and Me 3 SiCH 2 Li•(PMDTA) (PMDTA = pentamethyldiethylenetriamine, i.e., Me 2 NCH 2 CH 2 N(Me)CH 2 CH 2 NMe 2 ) were introduced to grow PS chains from (polyolefinyl) 2 Zn.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syntheses of polyethylene-block-polyester and polyethylene-block-polyether have been attempted with POs functionalized with -OH end groups, which were generated by treatment of the CCTP product (polyolefinyl) 2 Zn with O 2 [28][29][30][31]. We also discovered a method to grow polystyrene (PS) chains initiating from (polyolefinyl) 2 Zn that allows the syntheses of commercially more relevant PO-block-PS and PS-block-PO-block-PS in one-pot [32][33][34][35]. In those works, n-BuLi•(TMEDA) (TMEDA = tetramethylethylenediamine, i.e., Me 2 NCH 2 CH 2 NMe 2 ) and Me 3 SiCH 2 Li•(PMDTA) (PMDTA = pentamethyldiethylenetriamine, i.e., Me 2 NCH 2 CH 2 N(Me)CH 2 CH 2 NMe 2 ) were introduced to grow PS chains from (polyolefinyl) 2 Zn.…”
Section: Methodsmentioning
confidence: 99%
“…However, the amounts of the extracted homo-PSs were slightly higher (30-34% vs. 27-29%) and the molecular weight distributions of the extracted homo-PSs were broader than those in the case of pentylallyl-Li•(PMDTA) (M w /M n 1.38-1.52 vs. 1.23-1.25), indicating that pentylallyl-Li•(PMDTA) might be a better initiator than PhLi•(PMDTA) in growing PS chains from (polyolefinyl) 2 Zn. Previously, we introduced n-BuLi•(TMEDA) and Me 3 SiCH 2 Li•(PMDTA) as initiators for growing PS chains from the CCTP product (polyolefinyl) 2 Zn, mainly based on the model studies performed with R 2 Zn (R = Et, 1-hexyl, benzyl) [32,33]. Though significant performance differences could not be observed among pentylallyl-Li•(PMDTA), PhLi•(PMDTA), n-BuLi•(TMEDA), and Me 3 SiCH 2 Li•(PMDTA) in the model studies performed with (1-hexyl) 2 Zn (Table 2), the studies performed with actual (polyolefinyl) 2 Zn indicated that pentylallyl-Li•(PMDTA) and PhLi•(PMDTA) were superior to the previous initiators.…”
Section: Synthesis Of Po-block-psmentioning
confidence: 99%
“…The olen polymerization was performed using a typical ansa-metallocene catalyst (rac-[Me 2 Si(2methylindenyl) 2 ]ZrCl 2 ) activated with MMAO, which was reported to be effective in the CCTP with suppression of the undesirable b-elimination process. 15,53,54 Olen polymerization was performed by feeding ethylene gas into the system containing 1-octene or 1-pentene monomer. The catalyst worked efficiently, leading to consumption of almost all of the a-olen monomers, once the zinc species [4-(isopropenyl)benzyl] 2 Zn is sufficiently pure.…”
Section: Preparation Of Multiblock Copolymersmentioning
confidence: 99%
“…[11][12][13][14] Recently, we disclosed a novel method for direct preparation of PO-PS diblock copolymers using olen and styrene monomers, where coordination and anionic polymerizations were sequentially performed in one-pot (Scheme 1(b)). 15 The poly-olen chains were grown from dialkylzinc sites by the so-called 'coordinative chain transfer polymerization (CCTP)', [16][17][18][19][20] which is a useful tool for precise architectural design of polyolen chains. [21][22][23][24][25][26][27][28][29][30][31][32] The PS chains were subsequently grown from the zinc sites attached to the PO chains by feeding styrene monomer and a sub-stoichiometric amount of nBuLi(tmeda) (tmeda: N,N,N 0 ,N 0 -tetramethylethylenediamine) initiator (0.2 eq./Zn) into the system.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we previously designed a strategy for the direct synthesis of PO-PS diblock copolymers from olefin and styrene monomers that involved coordinative chain transfer polymerization (CCTP) and subsequent anionic polymerization of styrene in a one-pot system (Scheme 1a) [32]. CCTP is an established technology that is actively employed in olefin polymerization reactions where precise architectural design and end group functionalization are required [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%